Pemanfaatan Jamur Janggel sebagai Produk Olahan Nugget di Desa Sukosari Kidul Kecamatan Sumberwringin Kabupaten Bondowoso dalam KKN UNEJ 2023 Melalui Eksperimen dan Pelatihan - Adinda Oktavia Kusumaningrum; Aulia Putri Hidayat; Fitri Intani Mahsin; Ahmad Bagas Nur Hidayat; Astrid Dea Rashida; Ramadhani Wijaya; Vanya Oxalita Asan Putri; Alyana Ulfa Rahmawati; Yohanes Rifki Bagus Pangestu; Rosmayniar Anggraeni (Institut Teknologi dan Bisnis Semarang, 2023)
This article raises the topic of the use of janggel mushroom in Sukosari Kidul Village. The greatest potential in Sukosari Kidul Village is in the agricultural sector, which includes corn commodities. The abundance of corn, which increases continuously, is certainly accompanied by the waste generated due to its utilization, one of which is corn cobs. Corn cobs, as the residue from the corn harvest, have been used as a basic material for janggel mushroom cultivation. This article aims to describe the results in the form of new innovations regarding the processing of janggel mushrooms into nuggets. The method of processing janggel mushrooms into nuggets begins with direct observation of the community's condition and raw materials. The next step is to experiment with transforming the janggel mushrooms into a ready-to-eat derivative product in the form of nuggets. The production of this nugget-derived product is then used as training material for PKK members in Sukosari Kidul Village. That training was enthusiastically attended by 15 participants from PKK. Therefore, the researchers hope that this innovation can be utilized as a new idea for processed janggel mushrooms or as seeds of entrepreneurship in Sukosari Kidul.